Analytical methods for network congestion control - Low, Steven H. (Synthesis lectures on communication networks, 2017)
The congestion control mechanism has been responsible for maintaining stability as the Internet scaled up by many orders of magnitude in size, speed, traffic volume, coverage, and complexity over the last three decades. In this book, the authors develop a coherent theory of congestion control from the ground up to help understand and design these algorithms.